The Effect of Work Life Balance on Turnover Intention with Self-Efficacy As a Moderating Variable on Generation Z Employees - Nabila Absharina Herman Wr; Zainnur M. Rusdi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the influence of work-life balance on turnover intention among Generation Z employees in Indonesia, considering self-efficacy as a moderating variable. A total of 166 respondents aged 18–27 with a minimum of one year of work experience participated in this quantitative study. Using a causal-associative design, data were analyzed through Moderated Regression Analysis (MRA) with Hayes' Process Macro Model 1. The descriptive results showed moderate levels of work-life balance and turnover intention, and a high level of self-efficacy among participants. However, hypothesis testing revealed that work-life balance had no significant effect on turnover intention, and self-efficacy did not significantly moderate this relationship. These findings imply that, for Generation Z employees in Indonesia, turnover intention may be driven by factors beyond work-life balance and self-efficacy. The study underlines the complexity of turnover behavior in this demographic and encourages organizations to consider broader strategies, such as improving career development, fostering a positive organizational culture, and enhancing job satisfaction. Further investigation is needed to identify the most influential factors contributing to turnover intention, which will help organizations retain Generation Z employees more effectively.